Tubes still vital after all these years. - Symons, R.S (IEEE spectrum)
Though barely acknowledged in this solid-state world, vacuum tubes still rule where frequency is measured in gigahertz and power levels range upward from the kilowatt level. The author discusses the pros and cons of solid state devices and electron tubes. The benefits of tubes of solid state devices are outlined. Reliability and cathode exhaustion are also discussed